POPULATION PROJECTIONS: CHALLENGES IN FORECASTING DETERMINANTS OF DEMOGRAPHIC DEVELOPMENT IN THE CONTEXT OF SOCIO-POLITICAL CHANGES - Paunović Radulović, Dragana; Anđelković, Marija; Subotić, Stefan (Serbian political thought, 2024)
The population is a significant resource upon which the socio-economic development of a country is based. Understanding population characteristics, as well as the political, ideological, and sociological determinants that shape the pattern of demographic growth in the past and predict future trends, is essential for policy planning in various social fields. This paper focuses on population projections, which provide an image of how the size and structure of the population by age and sex might look in the future. The paper presents a theoretical-methodological approach to making population projections and the challenges that authors face when calculating them. Since the base population, representing the estimated number of inhabitants in the census year is fundamental to making projections, the socio-political context at the time of conducting the population census of Serbia is also considered, as it often impeded their complete and smooth implementation. Furthermore, challenges are present not only in forecasting future trends in fertility and mortality, particularly in determining future migration flows, which are influenced by both economic and political factors, but also in deciding which methods to use, what the optimal projection period should be, and at which territorial level to set hypotheses about the determinants of population movement. This paper aims to provide possible solutions to the challenges of forecasting future population trends and to highlight the importance of coordinated action from all segments of society, institutional cooperation, and joint resolution of strategic issues, including the most challenging ones, such as population policy measures and migration management strategies. Forecasting demographic trends at lower territorial levels is particularly important, as it forms the basis for development planning and reducing regional disparities at the level of local government units.